PENGINJILAN KONTEKSTUAL DAN PENANAMAN GEREJA RUMAH DI KAMBOJA PASCA-TRAUMA SOSIAL (Tarombo: Journal of Christian Theology, Education, and Ministry, 2026)
ABSTRACTThis study addresses the ineffectiveness of conventional propositional evangelism in post-genocide Cambodia, where the Khmer Rouge regime (1975–1979) caused the deaths of 1.7 to 2.5 million people and destroyed social trust. Despite decades of missionary efforts, Christians comprise less than 2% of Cambodia’s population, indicating a critical need for trauma-sensitive approaches. The research identifies a gap in integrating missiology, trauma psychology, and contextual ecclesiology, particularly regarding house churches as therapeutic spaces. Using a qualitative literature review and critical analysis of existing frameworks—including Hiebert’s critical contextualization, Zdero’s house church ecclesiology, and Van der Kolk’s trauma theory—this study develops the Post-Trauma Contextual Evangelism and House Church Planting Framework (PCE-HCP Framework). The novelty lies in positioning trauma as a theological starting point rather than an obstacle, articulating house churches as communal therapeutic spaces, and offering specific contextualization criteria for post-trauma societies. The framework integrates three pillars: contextualization principles, house church ecclesiology, and collective trauma recovery. This research contributes both academically, by filling the lacuna in Cambodian missiological studies, and practically, by providing a model for evangelism in post-trauma contexts across Southeast Asia.Keywords: contextual evangelism; house church; post-trauma society; Cambodia; missiologyABSTRAKPenelitian ini mengatasi ketidakefektifan penginjilan konvensional yang bersifat propositional di Kamboja pasca-genosida, di mana rezim Khmer Merah (1975–1979) menyebabkan kematian 1,7 hingga 2,5 juta jiwa dan menghancurkan kepercayaan sosial. Meskipun upaya misi telah berlangsung puluhan tahun, umat Kristen kurang dari 2% dari total populasi Kamboja, menunjukkan kebutuhan mendesak akan pendekatan yang sensitif terhadap trauma. Studi ini mengidentifikasi kesenjangan dalam integrasi misiologi, psikologi trauma, dan eklesiologi kontekstual, khususnya terkait gereja rumah sebagai ruang terapeutik. Melalui kajian literatur kualitatif dan analisis kritis terhadap kerangka yang ada—termasuk kontekstualisasi kritis Hiebert, eklesiologi gereja rumah Zdero, dan teori trauma Van der Kolk—penelitian ini mengembangkan Post-Trauma Contextual Evangelism and House Church Planting Framework (PCE-HCP Framework). Kebaruan terletak pada penempatan trauma sebagai titik awal teologis, artikulasi gereja rumah sebagai ruang terapeutik komunal, dan kriteria kontekstualisasi spesifik untuk masyarakat pasca-trauma. Kerangka ini mengintegrasikan tiga pilar: prinsip kontekstualisasi, eklesiologi gereja rumah, dan pemulihan trauma kolektif. Kontribusi penelitian ini bersifat akademik, dengan mengisi kekosongan studi misiologi Kamboja, dan praktis, dengan menyediakan model penginjilan untuk konteks pasca-trauma di Asia Tenggara.Kata kunci: penginjilan kontekstual; gereja rumah; masyarakat pasca-trauma; Kamboja; misiologi
Keywords: penginjilan konstekstual; gereja rumah; masyarakat pasca-trauma; kambija; misiologi